Campus Canopy, 1936-11-13 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1936)
Sanford at Assembly States College Aims -- Emily Woodward Speaks at Garden Club Meet -- Duncan Leads Ballot in Freshman Election -- Pine Cone Editor Reports Progress -- Seen at the Circus -- Kappas Win Twin Games; Leading the Lambdas Five Points -- Vocational Groups for Study Organized By Miss Thyrza Perry
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals